The Influences of Bio-stimulators Compounds on Growth Traits and Essential Oil Content of Rosemary (Rosmarinus officinalis L.) - A Foroutan nia; Mehrafarin; E Hadavi; H Naghdi Badi (Institue of Medicinal Plants, ACECR, 2014)
Background: Rosemary (Rosmarinus officinalis L.) as a member of the Lamiaceae family is a valuable aromatic and medicinal plant which is cultivated in large scale in Iran. Therefore, it is necessary to determine influence of factors affecting plant growth and drug metabolite production. Objectives: This experiment was carried out to evaluate the effects of bio-stimulators compounds on growth and phytochemical traits of rosemary (Rosmarinus officinalis L.). Methods: This experiment was conducted on the basis of randomized complete blocks design with three replications at Medicinal Plants Institute (MPI) of ACECR in 2013. The treatments included commercial formulations of aminolforte, kadostim, fosnutren, humiforte (each of them at 0.75 and 1.5 L.ha-1), 120 kg.ha-1 chemical fertilizers (N.P.K, 15:8:15%), and control treatment (without any bio-stimulators and chemical fertilizer applications). Results: The effects of treatments were significant (p≤0.01) on all of the traits in a way that the maximum value of plant height (42.94 cm), leaf length (34.92 mm), leaf width (4.2 mm), number of leaves per plant (465 leaves.plant-1), leaf SPAD value (56.1 SPAD), total dry weight (246.78 kg.ha-1) essential oil (1.4%), α-pinene (27.35%), was obtained by foliar application of 1.5 L.ha-1 fosnutren. Also, the highest of collar diameter of stem (10.77 mm) and number of branches per plant (24.63 branches.plant-1) and camphor (9.87%) was observed in chemical fertilizers treatment, 1.5 L.ha-1 aminolforte and humiforte, respectively. In contrast, the least amounts of traits were observed in control treatment. Conclusion: The growth and phytochemical traits of rosemary increased due to foliar application of bio-stimulators compounds.